Anti-Corrosive Coating Prepared from Hydroxy Terminated Polybutadiene - GOURANLOU, FARIDEH (Asian Journal of Chemistry, 2010)
Hydroxyterminated polybutadiene coating has good properties as strong adhesion, resistance against bases and dilute acids, salty water, and solvents. The coating also has insulating properties against electricity and use to varnish coating.